Theoretical investigation of selective inhibitory activity of chromone-based compounds against monoamine oxidase (MAO)-A and -B - Putri, Intan Salsabila; Shamsudin, Nur Farisya; Abdullah, Maryam Aisyah; Nurcholis, Mochamad; Imran, Syahrul; Yu, Chai Xin; Tham, Chau Ling; Ibrahim, Zalikha; Taher, Muhammad; Rullah, Kamal; Mohd Aluwi, Mohd Fadhlizil Fasihi; Leong, Sze-Wei; et al. (Taylor and Francis Ltd., 2024)
Monoamine oxidase (MAO) is crucial for the breakdown of monoamine neurotransmitters, making it a promising target for treating neurodegenerative disorders, such as depression, Alzheimer’s disease, and Parkinson’s disease. In this study, we investigated the selective inhibitory activity of chromone-based compounds against MAO-A and MAO-B for neurodegenerative disease treatment. In literary sources, thirty chromone derivatives have been identified as potential ligands for MAO-A and MAO-B inhibitors. We utilized molecular docking to evaluate how the most active compound interacted with the targeted MAO-A and MAO-B. Compound 2 g, the most active for MAO-A, demonstrated a lower CDOCKER energy compared to the co-crystallized ligand. Meanwhile, compound 2f, the most active for MAO-B, showed a CDOCKER energy similar to the co-crystallized ligand and exhibited similar binding patterns. Furthermore, we constructed a quantitative structure-activity relationship (QSAR) model to predict the properties and estimate IC50 values for 30 chromone derivatives functioning as MAO-A and MAO-B inhibitors. The model predictions were validated against experimental measurements. Our 2D QSAR model demonstrated robustness, with a statistically significant non-cross-validated coefficient (r2 < 0.9), cross-validated correlation coefficient (q2 < 0.6), and predictive squared correlation coefficient (r2pred < 0.8). Additionally, MD simulations confirmed the stable binding of compounds 2 g and 2f with MAO-A and MAO-B, respectively, displaying substantial binding energy. The most effective pharmacophore model identified key features, such as hydrogen bond acceptors and hydrophobic interactions, that contribute significantly to inhibitory potency. This study offers valuable insight into the selection of compounds with improved selectivity for MAO inhibition.